Skills and jobs in the Internet economy (Paris, 2014)
"Both generic and specialised ICT skills are becoming an important requirement for employment across the economy as the Internet becomes more engrained in work processes, but a significant part of the population lacks the basic skills necessary to function in this new environment. This paper examines the impact of the Internet on the labour market in this context. For example, between 7% and 27% of adults have no experience in using computers or lack the most elementary computer skills, such as the ability to use a mouse. In addition, the groups with the least ICT skills tend to be among the demographic groups at the most risk of losing jobs. Data also highlight a potential skills mismatch among those with the strongest ICT skills (youth) and those who actually use them at work (prime age and older adults)."